Improving the Life Skills of Students of SMK Negeri 1 Barru through Training in Making Liquid Organic Fertilizers: Peningkatan Life Skill Siswa SMK Negeri 1 Barru melalui Pelatihan Pembuatan Pupuk Organik Cair - Yusniar Rasjid; Zulkifli Rais; A. Bida Purnamasari; Rusdianto (Yayasan Ahmar Cendekia Indonesia, 2021)
The purpose of this activity is to seek to develop skills and abilities in the manufacture of liquid organic fertilizers as an effort to reduce environmental pollution caused by household waste and industrial waste. Lack of skills in making organic liquid fertilizer from household waste for students is the driving force for the implementation of this training activity. For this reason, this activity will provide training on how to make liquid organic fertilizer from household waste and rotten fruits. The results achieved were in the form of knowledge and skills on how to make organic liquid fertilizer from household waste and rotten fruits by involving students at school. This can be seen from the results of the participants' independent work in producing the final product in the form of liquid organic fertilizer. These students' skills can be seen from the results of independent work in forming attractive and beautiful horticulture plants. The results of the activity are also in the form of enthusiasm and enthusiasm of the students/training participants which can be seen from the presence of the participants and interest in the practice of making organic liquid fertilizer from waste. Abstrak: Tujuan kegiatan ini yaitu hendak mengupayakan pengembangan keterampilan dan kemampuan dalam pembuatan pupuk organik cair sebagai upaya mengurangi pencemaran lingkungan akibat limbah rumah tangga dan limbah industri. Kurangnya keterampilan dalam membuat pupuk cair organik dari limbah rumah tangga bagi siswa menjadi pendorong pelaksanaan kegiatan pelatihan ini. Untuk itu, kegiatan ini akan memberikan pelatihan cara pembuatan pupuk organik cair dari limbah yang berasal dari rumah tangga dan buah-buahan yang busuk. Hasil yang dicapai berupa pengetahuan dan keterampilan cara membuat pupuk cair organik dari limbah rumah tangga dan buah-buahan busuk dengan melibatkan siswa-siswa di sekolah. Hal tersebut tampak dari hasil kerja mandiri peserta dalam menghasilkan produk akhir berupa pupuk organik cair. Keterampilan siswa tersebut tampak dari hasil kerja mandiri dalam membentuk tanaman vertikultur yang menarik dan indah. Hasil kegiatan juga berupa antusiasme dan semangat siswa/ peserta pelatihan yang tampak dari kehadiran peserta dan ketertarikan dalam praktek pembuatan pupuk cair organik dari limbah.